Radioelectric asymmetric brain stimulation and lingual apex repositioning in patients with atypical deglutition - Castagna A; Rinaldi S; Fontani V; Mannu P (Journal of Multidisciplinary Healthcare, 2011)
Alessandro Castagna1, Salvatore Rinaldi1,2, Vania Fontani1, Piero Mannu11Rinaldi-Fontani Institute, 2School of Occupational Medicine, University of Florence, Florence, ItalyBackground: Atypical deglutition is exacerbated by stress and anxiety. Several therapeutic approaches have been employed to treat stress and anxiety disorders, ranging from typical psychopharmacological strategies to novel physical protocols, such as transcranial magnetic stimulation and radioelectric asymmetric conveyor (REAC) stimulation. The purpose of the present study was to test the efficacy of REAC brain stimulation in atypical deglutition.Methods: The position of the lingual apex (Payne method), pattern of free deglutition, and subjective and objective impression of deglutition were evaluated in 128 outpatients suffering from atypical deglutition. Deglutition testing consisted of an operator holding down the lower lip, hence counteracting the strength exerted by the orbicularis muscle. All subjects were treated using two REAC brain stimulation protocols. Patients were assessed before treatment, immediately after treatment, and three months following the last cycle of REAC therapy.Results: REAC stimulation led to an improvement in positioning of the lingual apex and a significant decrease of muscle involvement in all patients immediately after REAC treatment, and the improvement was maintained at three-month follow-up.Conclusion: In the present study, the REAC therapeutic protocols led to normalization in lingual apex positioning and significant improvement in swallowing in all participants suffering from atypical deglutition.Keywords: atypical deglutition, stress, anxiety, radioelectric asymmetric brain stimulation